A Systematic Review of Reimbursement Mechanisms: Effectiveness, Efficiency, and Patient Satisfaction in Insurance-Based Health Financing Systems - Neliyana Neliyana; Ummi Kalsum; Asparian Asparian; Dwi Noerjoedianto; Wilia Novita Eka Rini; Muldiasman Muldiasman (Rifa'Institute, 2026)
Introduction: The reimbursement mechanism is a fundamental component in an insurance-based financing system that affects service effectiveness, operational efficiency, and patient satisfaction. Objective: This study aims to conduct a systematic review of the literature that discusses reimbursement mechanisms with a focus on these three main dimensions. Method: Using the Systematic Literature Review approach following the PRISMA 2020 guidelines, a comprehensive search was conducted through four electronic databases to identify peer-reviewed articles for the 2021-2025 period. Of the 30 articles initially identified, six studies met the inclusion criteria and were analyzed in depth. Results and Discussion: Results show that the Diagnosis Related Groups system is effective in reducing costs but has the potential to negatively impact the quality of service. Differential reimbursement and cost-sharing mechanisms have been shown to be able to direct healthcare seeking behavior, although their effectiveness is highly contextual dependent on geographic and socio-economic factors. Patient satisfaction shows significant variation by service class with disparities in the dimensions of effectiveness, accessibility, patient-centeredness, and equity. The utilization rate of health services in Indonesia's National Health Insurance system is still relatively low, indicating the need for a comprehensive evaluation of the design of reimbursement mechanisms. Conclusion: This study emphasizes that optimizing the reimbursement system requires a holistic approach that balances cost efficiency, service quality, and patient satisfaction as interrelated outcomes in the health financing ecosystem